An Analysis on Women’S Participation In Swadeshi Movement: a Case Study of India’S Freedom Struggle: Examining the Role of Women in India's Swadeshi Movement (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Thehistory of Indian Freedom Movement would be incomplete without mentioning thecontributions of women. The sacrifices made by the women of India will occupythe foremost place. They fought with true spirit and undaunted courage andfaced various tortures, exploitations and hardships to earn us freedom.Swadeshi movement was one of the major events in the History of Indian FreedomMovement. It was started in 1905 as an agitation against the partition ofBengal and it spread to other parts of the country including Maharashtra. TheSlogans of Swaraj, the concepts of boycott, National Education and the spiritof Swadeshi were spread from Bengal to Maharashtra along with other regions.